Trends in salivary gland tumors among Jordanians: A retrospective multi-institutional study - hajeer, Manar; jaber, Omar; A Al-Nahar, Lina; Aljarrah, Duaa; AlQudah, Mohammad; Alarjat, Jamal; Matalka, Ismail; M. Almasri, Nidal; A. Al-Abbadi, Mousa (Jordan Medical Journal, 2025)
Background: Salivary gland tumors are uncommon. To the best of our knowledge, little data are available on the demographics and histopathological distribution of these tumors in Jordan. This study aimed to investigate the clinicopathological aspects of different salivary gland tumors diagnosed in four large Jordanian medical institutions, and to compare our findings with those from different countries. Materials and Methods: Patients (N= 410) with surgically removed or biopsied salivary gland tumors, diagnosed between 2008 and 2018, were included in a retrospective analysis of the patient’s demographics, tumor site, and histopathology type. Corresponding data were retrieved from the archives of the four major referral Jordanian institutions: Jordan University Hospital, King Hussein Cancer Center, King Abdullah University Hospital, and King Hussein Medical City. Results: The mean age for patients was 46.3 years. Only 6.6% of the cases were for patients younger than 20. Malignancies were found in 59.3% of the cases. The male-to-female ratio was 1.15:1.0. Benign tumors were more common than malignant tumors (69 %), the most frequent of which was pleomorphic adenoma (61.5%), which was more commonly identified in females (62.1%). Warthin’s tumor was the second frequent type; it was more commonly seen in males (87.1%). Mucoepidermoid carcinoma was the most common malignant tumor (34.9%). Most of the tumors originated from the parotid glands (85.6%), with a clear predominance of benign tumors. Conclusion: Our results are in alignment with most studies and slightly different from others, supporting the hypothesis that there is a geographic variation in tumor distribution.